The Role of Governance of Guidance And Counseling Services For High School Students In Balikpapan - Halimi Firdausi (Institute of Computer Science (IOCS), 2021)
Guidance and counseling play an important role in the growth and development of the educational process in the school environment, because the purpose of the counseling guidance program is to assist individuals in developing their various abilities, besides that the performance of guidance and counseling teachers is described as a professiot has high work standards. can describe the quality that must be produced based on the structure and quality of work in accordance with the professional code of ethics so that the counselor is said to be professional or qualified in carrying out his services. This study uses a descriptive method with a qualitative approach and data triangulation analysis, the results of the study explain that the concept of guidance and counseling is an important part in the school environment, this role is also a center for personality and career development for all students, Counseling Guidance Services in the school environment Of course, it is not only focused on providing and directing students who have disciplinary actions, but these services are also functioned as regulators of order and policy determination in the school environment as a whole, the concept of governance has a view on indicators regulating, designing, managing up to evaluating, as for some Guidance and Counseling services that are implemented in the school environment, including orientation services, information services, placement and distribution services, besides that the concept of counseling guidance can also be integrated through several several subjects, one of which is the subject of Islamic Religious Education